Survival Analysis and Risk Prediction Model for Tuberculosis Development in HIV-Infected Patients - Kittikun, Kanreuthai; Siangchin, Pornchanan; Kaglai, Kittin; Punsuwan, Niramon (Disease Control Journal, 2025)
HIV/TB coinfection is a significant public health problem in Thailand. Understanding risk factors and predicting tuberculosis (TB) development is therefore essential for developing effective strategies. The objective of this study was to analyze TB - free survival time and to develop a risk prediction model for TB in HIV-infected patients in Thailand. This retrospective cohort study utilized data from the National AIDS Program (NAP) database from 2009 to 2023 (B.E. 2552 to 2566), analyzing data from 289,847 HIV- infected patients. Kaplan-Meier survival analysis revealed that the TB-free Restricted Mean Survival Time (RMST) was approximately 9 years. The developed Cox proportional hazards model effectively predicted the risk of TB development in HIV-infected patients in Thailand. Significant risk factors for TB development identified by the Cox proportional hazards analysis included older age, male sex, symptomatic HIV infection and AIDS stage (compared to asymptomatic stage), presence of other opportunistic infections, and use of alternative drug regimens. Conversely, higher CD4 count, receiving ART, and ART initiation within 1 week of diagnosis were significant protective factors. These findings can help identify high-risk individuals for targeted surveillance, potentially leading to a reduction in TB incidence and further improving clinical outcomes in this patient population.